Correlative analysis of nanoparticle tracking, flow cytometric and functional measurements for circulating microvesicles in normal subjects. Issue 145 (September 2016) - Enjeti, Anoop K.; Ariyarajah, Anita; D'Crus, Angel; Seldon, Michael; Lincz, Lisa F.
Abstract: Introduction: Circulating microvesicles (MV) can be analysed using a number of different techniques. The aim of this study was to evaluate the correlation between functional procoagulant based assays including thrombin generation, factor Xa activation test (XaCT), and phosphatidylserine factor Xa-activity by ELISA with optical MV enumeration by flow cytometry and nanoparticle tracking analysis. Methods: Citrated blood samples were collected from 60 healthy volunteer blood donors after informed consent. Platelet free plasma was prepared using a standardized published protocol. MV subsets were enumerated by flow cytometry (BDFACS Canto) after staining with specific antibodies for platelets (CD41), endothelial cells (CD105), red cells (CD235) monocytes (CD14), tissue factor (CD142) and for phosphatidylserine expression by binding to annexin V. A standardized protocol using counting beads was employed. Nanotracking analysis was performed on both scatter and fluorescent settings after MV staining with quantum dot stain, Qdot 655. Procoagulant function was assessed by the XaCT assay on an automated coagulation analyser and by thrombin generation assay measuring endogenous thrombin potential (ETP), lagtime, peak (PEAK) and time to peak (ttPEAK) using a Calibrated Automated Thrombogram (CAT). The statistical analysis was carried out with Statistica 12 software using non-parametric tests (Spearman rank order correlations, with significance set at p < 0.05). Results: In normal healthy subjects, thrombin generation parameters correlated with levels of MV measured by flow cytometry. ETP, lagtime, ttPEAK and PEAK correlated with MV expressing phosphatidylserine (rs, Spearman rank order correlation was 0.29, 0.40, 0.31 and 0.34 respectively, p < 0.05), and MV expressing tissue factor (rs was 0.29, 0.40, 0.31 and 0.34 respectively, p < 0.05), whilst red cell derived MV correlated with lagtime, ttPEAK and PEAK (rs, was 0.35, 0.30 and 0.3, respectively, p < 0.05). Lagtime and ttPEAK negatively correlated with the clot based XaCT test (rs, was − 0.34 and − 0.30 respectively, p < 0.05) and positively correlated with the ELISA MP-activity assay (rs = 0.42 for both, p < 0.05). In addition, endothelial MV levels weakly correlated with white cell counts (rs = 0.27, p < 0.05). Conclusions: Thrombin generation and flow cytometry for phosphatidylserine or tissue factor expressing MV correlate well as markers for procoagulant activity. A combination of optical or non-optical enumeration as well as functional methods may be required for a complete profiling of circulating MV. Highlights: Thrombin generation correlates well with flow cytometry for PS or TF expressing MV in normal subjects. Flow cytometry for PS and TF expression MV by flow could be surrogate markers for procoagulant activity of microvesicles. A combination of optical and functional methods should be used for assessment of microvesicles.